Mechanistic Insights into Flavonoid Subclasses as Cardioprotective Agents Against Doxorubicin-Induced Cardiotoxicity: A Comprehensive Review - Shang W; Li XH; Zeng LH; Li Z; Hu Y; Wen HM; Cao FJ; Wan GX (Drug Design, Development and Therapy)
Wei Shang,1,* Xin-Hui Li,2,* Lang-Hong Zeng,2,* Zhi Li,3 Yu Hu,2 Hui-Min Wen,2 Feng-Jun Cao,2 Guo-Xing Wan2 1Department of Orthopedics, Renmin Hospital, Hubei University of Medicine, Shiyan, 442000, People’s Republic of China; 2Department of Oncology, Renmin Hospital, Hubei University of Medicine, Shiyan, 442000, People’s Republic of China; 3Department of Cardiology, The First Affiliated Hospital of Shantou University Medical College, Shantou, 515041, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guo-Xing Wan; Feng-Jun Cao, Department of Oncology, Renmin Hospital, Hubei University of Medicine, 39# Chaoyang Road, Shiyan, Hubei, 442000, People’s Republic of China, Tel/Fax +86 719 8637385, Email 15gxwan@stu.edu.cn; fengjuncaoshiyan@126.comAbstract: Doxorubicin (DOX) is an anthracycline chemotherapeutic agent widely used for treating various malignancies due to its remarkable efficacy. However, the dose-limiting cardiotoxicity induced by DOX remains a critical clinical concern with limited therapeutic strategy. Several molecular mechanisms underlying the pathogenesis of doxorubicin-induced cardiotoxicity (DIC) have been proposed, including oxidative stress, dysregulation of Top2β, mitochondrial damage, imbalance of calcium homeostasis, ferroptosis, and inflammatory responses. Increasing studies have posed the promise of the natural products flavonoids against DIC attributed to its advantages in antioxidant activity as well as anti-cancer properties. This paper reviews relevant publications to date and comprehensively summarizes the evidence from preclinical and clinical studies in support of the cardioprotective effect of seven flavonoids subclasses against DIC, including flavones with 18 compounds, flavonols with 11 compounds, isoflavones with 7 compounds, flavanones with 6 compounds, chalcones with 3 compounds, flavanols with 2 compounds and anthocyanins with 2 compounds. Specially, several lines of evidence have also demonstrated the anti-cancer property of flavonoids in addition to the cardioprotective property. This review synthesizes comprehensive mechanistic and translational insights to inform future preclinical and clinical investigations aiming at integrating flavonoid-based interventions into oncotherapeutic regimens. The accumulated evidence underscores flavonoids as promising candidates for DIC as well as adjuvant cancer therapy.Keywords: doxorubicin, cardiotoxicity, flavonoids, mechanism, cardioprotection